2010
DOI: 10.1016/j.medengphy.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

A musculoskeletal shoulder model based on pseudo-inverse and null-space optimization

Abstract: ARTICLE IN PRESSThe goal of the present work was assess the feasibility of using a pseudo-inverse and null-space optimization approach in the modeling of the shoulder biomechanics. The method was applied to a simplified musculoskeletal shoulder model. The mechanical system consisted in the arm, and the external forces were the arm weight, 6 scapulo-humeral muscles and the reaction at the glenohumeral joint, which was considered as a spherical joint. The muscle wrapping was considered around the humeral head as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
8

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 43 publications
2
29
1
8
Order By: Relevance
“…The optimisation method minimises muscle stresses and is therefore referred to as the stress-based method in the following. The work was realised on a 3D model of the glenohumeral joint (Terrier et al 2007(Terrier et al , 2010(Terrier et al , 2013, which is used to analyse issues related to total shoulder arthroplasty. The model has the ability to predict glenohumeral stability through the evaluation of humeral head translation.…”
Section: Introductionmentioning
confidence: 99%
“…The optimisation method minimises muscle stresses and is therefore referred to as the stress-based method in the following. The work was realised on a 3D model of the glenohumeral joint (Terrier et al 2007(Terrier et al , 2010(Terrier et al , 2013, which is used to analyse issues related to total shoulder arthroplasty. The model has the ability to predict glenohumeral stability through the evaluation of humeral head translation.…”
Section: Introductionmentioning
confidence: 99%
“…This problem is particularly present for the shoulder, which has a wide range of motion, and many muscles. As for other joints, three techniques are used: 1) group muscles to suppress the indeterminacy (Inman et al, 1944), 2) use inverse dynamics coupled with optimization of a cost function (Charlton and Johnson, 2006;Dickerson et al, 2007;Favre et al, 2005;Holzbaur et al, 2005;Karlsson and Peterson, 1992;Terrier et al, 2010;van der Helm, 1994), or 3) use forward dynamics with electromyography (EMG) measurements as input (Langenderfer et al, 2005;Laursen et al, 1998;Terrier et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The null-space method was used both because it has shown promising results (Aeberhard et al 2009;Terrier et al 2010) and because it helped to pinpoint the nature of the unfeasibility observed in Ingram et al (2012) due to its direct use of the map (13) to construct the solution.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed presentation of this re-parameterisation is given in Aeberhard et al (2009) andTerrier et al (2010).…”
Section: Null-space Optimisationmentioning
confidence: 99%